The family of Awlad Muhammad and its political and economic role in the western province of Tripoli, 1550-1813 - Radhiwi, Dr. Munther Obaid (Thi Qar Arts Journal, 2022)
This research sheds light on a family that influenced the history of the western Tripoli Eyale in general and the Fezzan region in particular, the family of Muhammad al-Fassi’’s sons, which extended its control over the province of Fezzan for a period of nearly two hundred and fifty years (1550-1813). This family had an active and prominent role in The political and economic events in the Fezzan region throughout that period, they engaged in a bitter struggle with the Ottomans (1551-1711) and the Karamanids (1711-1813) for control of Fezzan, and the repeated attempts of the ruling authorities in Tripoli failed to eliminate the rule of Muhammad’ sons, Because of the strength of their influence in Fezzan, until the coming of Yusuf Pasha al-Qarmanli to power in Tripoli (1795-1833), who took advantage of the weakness that this family had become, and was able to end their rule.